Critical raw material resources in Nugrus-Sikait area, South Eastern Desert, Egypt: Geological and geochemical aspects. (January 2023) - Khaleal, Farrage M.; Lentz, David R.; Kamar, Mohamed S.; Saleh, Gehad M.; Lasheen, El Saeed R.
Abstract: The current work aims to assess the critical raw materials (CRMs) in the Arabian-Nubian Shield in accordance with the European Union. CRMs are strategically and economically significant, but they are subject to supply shortages. CRMs, such as Nb, Ta, Zr, U, Th, Rb, Ga, Hf, Zn, Ba, Sr, Sn, Cu, and Pb, are concentrated in post-orogenic highly fractionated granitic plutons, such as Abu Dabbab, Abu Diab, Homrit Waggat, Um Naggat, and Nuweibi. They also occur in the gneiss rocks of the Nugrus-Sikait area. The present work sheds light on the CRM resources in the Nugrus-Sikait area in the South Eastern Desert, Egypt. Gneiss rocks, ophiolitic rocks (ultramafics, metagabbros, schists, and mélange), gneissose biotite granites, muscovite leucogranites, pink biotite granites, and post-granitic dikes and veins are the main exposed rock units in the target area. CRMs are abundant in the examined area and reach up to 1845 ppm Nb, 203 ppm Ta, 3212 ppm Zr, 1789 ppm Y, 278 ppm Hf, 3209 ppm Zn, ˃10000 ppm Pb, 941 ppm Sn, 1458 ppm Cu, 3551 ppm U, 2233 ppm Th, 144 ppm Sr, 1416 ppm Rb, and 121 ppm Ba. Therefore, it's recommended to shed light on CRMs distribution due to their economic importance and strategic uses. Highlights: Critical raw materials (CRMs) are strategically significant but they are subject to supply shortage. CRMs are abundant in the Arabian Nubian Shield certainly in Nugrus-Sikait area. Abu Rusheid gneiss rocks contain the highest CRMs concentrations in accordance to European Union.